Assessing the impact of diagenesis on δ11B, δ13C, δ18O, Sr/Ca and B/Ca values in fossil planktic foraminiferal calcite. (1st October 2015) - Edgar, Kirsty M.; Anagnostou, Eleni; Pearson, Paul N.; Foster, Gavin L.
Abstract: The geochemical composition of foraminiferal tests is a valuable archive for the reconstruction of paleo-climatic, -oceanographic and -ecological changes. However, dissolution of biogenic calcite and precipitation of inorganic calcite (overgrowth and recrystallization) at the seafloor and in the sediment column can potentially alter the original geochemical composition of the foraminiferal test, biasing any resulting paleoenvironmental reconstruction. The δ 11 B of planktic foraminiferal calcite is a promising ocean pH-proxy but the effect of diagenesis is still poorly known. Here we present new δ 11 B, δ 13 C, δ 18 O, Sr/Ca and B/Ca data from multiple species of planktic foraminifera from time-equivalent samples for two low latitude sites: clay-rich Tanzanian Drilling Project (TDP) Site 18 from the Indian Ocean containing well-preserved ('glassy') foraminifera and carbonate-rich Ocean Drilling Program (ODP) Site 865 from the central Pacific Ocean hosting recrystallized ('frosty') foraminifera. Our approach makes the assumption that environmental conditions were initially similar at both sites so most chemical differences are attributable to diagenesis. Planktic foraminiferal δ 18 O and δ 13 C records show offsets in both relative and absolute values between the two sites consistent with earlier findings that these isotopic ratios are strongly influenced by diagenetic alteration. Sr/Ca and B/Ca ratios in planktic foraminiferal calcite are also offset between the two sites but there is little change in the relative difference between surface and deep dwelling taxa. In contrast, δ 11 B values indicate no large differences between well-preserved and recrystallized foraminifera suggesting that despite extensive diagenetic alteration the δ 11 B of biogenic calcite appears robust, potentially indicative of a lack of free exchange of boron between pore fluids and the recrystallizing CaCO3 . Our finding may remove one potential source of uncertainty in δ 11 B based pH reconstructions and provide us with greater confidence in our ability to reconstruct pH in the ancient oceans from at least some recrystallized foraminiferal calcite. However, further investigations should extend this approach to test the robustness of our findings across a range of taphonomies, ages and burial settings.